Corrosion Behavior of Copper Exposed in Marine Tropical Atmosphere in Rapa Nui (Easter Island) Chile 20 Years after MICAT - Rosa Vera; Bárbara Valverde; Elizabeth Olave; Andrés Díaz-Gómez; Rodrigo Sánchez-González; Lisa Muñoz; Carola Martínez; Paula Rojas (Metals, 2022)
Atmospheric corrosion of copper, exposed on a tropical island in the South-Central Pacific Ocean, was reported and compared with those of a very similar study at the same site conducted 20 years earlier. The new measurements—taken over three years of exposure, from 2010 to 2013—quantified corrosion by mass loss, characterized corrosion products by X-ray diffraction (DRX) and Raman techniques, observed the attack morphology by Scanning Electron Microscope (SEM), and evaluated the patina resistance using electrochemical techniques. The results showed a copper corrosivity category of C4, and the main copper patina compound, cuprite, was porous, nonhomogeneous, and thin. Electrochemical measurements showed cuprite layer growth as a function of the exposure time, and the morphology did not favor corrosion protection. Finally, when comparing the results to those of a study 22 years previous, the copper corrosion rates increased only slightly, even with increased contaminants associated with growing local populations and continuous tourism on the island.